SentiFul: Generating a reliable lexicon for sentiment analysis - Neviarouskaya, A.; Prendinger, H.; Ishizuka, M. (2009 3rd International Conference on Affective Computing and Intelligent Interaction and Workshops, 2009)
The main drawback of any lexicon-based sentiment analysis system is the lack of scalability. Thus, in this paper, we will describe methods to automatically generate and score a new sentiment lexicon, called SentiFul, and expand it through direct synonymy relations and morphologic modifications with known lexical units. We propose to distinguish four types of affixes (used to derive new words) depending on the role they play with regard to sentiment features: propagating, reversing, intensifying, and weakening.